2023
DOI: 10.1136/bmjresp-2023-001738
|View full text |Cite
|
Sign up to set email alerts
|

The ‘ABC’ of respiratory disorders among adult Indigenous people: asthma, bronchiectasis and COPD among Aboriginal Australians – a systematic review

Abstract: BackgroundAboriginal Australians are reported to have higher presence of chronic respiratory diseases. However, comprehensive evidence surrounding this is sparse. Hence, a systematic review was undertaken to appraise the current state of knowledge on respiratory health in the adult Aboriginal Australians, in particular among the three most common respiratory disorders: asthma, bronchiectasis and chronic obstructive pulmonary disease (COPD).MethodsA systematic review of primary literature published between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Indigenous patients are reported to have a heightened burden of chronic respiratory diseases, alongside lower lung function parameters, including quite advanced and complex radiology findings 6,18–27 . In this case study, a significant proportion of patients were observed to have emphysema or bronchiectasis and to demonstrate cysts that in the majority were considered to be distinct either from emphysema or bronchiectasis.…”
Section: Discussionmentioning
confidence: 80%
“…Indigenous patients are reported to have a heightened burden of chronic respiratory diseases, alongside lower lung function parameters, including quite advanced and complex radiology findings 6,18–27 . In this case study, a significant proportion of patients were observed to have emphysema or bronchiectasis and to demonstrate cysts that in the majority were considered to be distinct either from emphysema or bronchiectasis.…”
Section: Discussionmentioning
confidence: 80%
“…In the global non-Indigenous populations, hospital admission data and factors associated with mortality, including the economic burden secondary to bronchiectasis are well documented [ 3 7 , 19 23 ]. Among the adult Indigenous population however, literature surrounding hospital admissions is sparse – despite a higher burden of chronic respiratory disease [ 10 , 24 ]. On the backdrop of poorer socioeconomic environment, alongside geographic, social and systemic barriers to healthcare, Indigenous people typically display a greater degree of multimorbidity, which in turn may alter the way in which respiratory diseases manifest in comparison to their non-Indigenous counterparts [ 28 , 31 , 42 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presence of bronchiectasis can lead to a greater number of hospitalisations and associated mortality both as direct results of bronchiectasis exacerbations per se or as an indirect contributor to other comorbidities [ 19 23 ]. Among both Aboriginal Australians and among Indigenous populations worldwide the prevalence of multimorbidity is high [ 24 27 ]. Indeed, concurrent presence of bronchiectasis and chronic obstructive pulmonary disease (COPD) has been reported in up to 50% of adult Aboriginal Australians [ 28 – 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite different ancestries, different histories and huge differences in environmental exposures, there is a remarkably consistent pattern of morbidity, including hypertension, diabetes mellitus, mental health disorders and high rates of suicide, and chronic respiratory disease 1 . Lung diseases that have been particularly well characterized in Indigenous populations include bronchiectasis and chronic obstructive pulmonary disease (COPD) 2 …”
mentioning
confidence: 99%